ANALISIS PENENTUAN PRIORITAS PEMELIHARAAN KRI DALAM MENDUKUNG KEBERHASILAN PELAKSANAAN TUGAS ANGKUTAN LAUT MILITER - Karadona Karadona; Danang Marsudi; Bambang Dilianto (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The main task of TNI is to uphold the sovereignty of the state. The success of the implementation of military sea transportation tasks cannot be separated from the readiness of KRI elements in supporting the implementation of operations. The purpose of this research is to analyze the Priority Determination of KRI Maintenance at the Depot Level at Kolinlamil to Support the Successful Implementation of Military Sea Transportation Tasks. The method used in this research is quantitative and data processing using SPSS 25 and AHP application programs. Samples will be taken from several crew members of KRI ABN-503, TMO-537, THG-538, I KBI-971 and KRI TBN-520. The research sample using AHP software amounted to 10 people and the determination of the number of samples using the Slovin formula was 90 respondents. The results of the study show that the turnaround time, airworthiness and technical conditions affect the success of carrying out the duties of Military Sea Transport. Partially rotating hours have a contribution of 31%, eligibility has a contribution of 25.3% and technical conditions have a contribution of 39.2%. Meanwhile, when tested simultaneously, the rotational hours, feasibility and technical conditions contributed 58.5% to the success of the Military Sea Transport. And for the results of the Analytical Hierarchy Process the influential variables in determining the priority of the KRI hardepo are turning hours, airworthiness and technical conditions and the alternative variables consist of KRI Teluk Amboina-503, KRI Teluk Bintuni-520, KRI Teluk Manado-537, KRI Teluk Hading-538 and KRI Tanjung Kambani-971. Based on the results, super Decision KRI Tanjung Kambani-971 became the main priority with a priority value of 0.37567 and 0.35875 based on the results of Super Decision software analysis. KRI Teluk Amboina-503 is the second priority with a priority value of 0.13454 and 0.13447 based on the results of Super Decision software analysis. KRI Teluk Bintuni-520 became the third priority with a priority value of 0.13454 based on the results of Microsoft Office Excel analysis and 0.13447 based on the results of Super Decision software analysis. KRI Teluk Manado-537 is the fourth priority with a priority value of 0.13068 based on the results of Microsoft Office Excel analysis and 0.12901 based on the results of Super Decision software analysis. KRI Tanjung Hading-538 is the fifth/last priority with a priority value of 0.11846 based on the results of Microsoft Office Excel analysis and 0.11559 based on the results of Super Decision software analysis.